PENINGKATAN PERFORMA KESTABILAN HEXACOPTER DENGAN SISTEM MRAC - Ikhwan Hidayatullah (Ensiklopedia of Journal, 2023)
This research studiesthe control of a hexacopter type aircraft using an adaptive PID system. To improve the stability performance of thr hexacopter. Increase the stability of the hexacopter type by tunning the PID constant. PID constant tunning automatically by applying the reference adaptive control (MRAC) method. The results of the hexacopter stability system research use static PID constants with Kp = 1.45, Ki = 1.30 and Kd = 0.34. Not yet able to adapt to environmental changes and component characteristics. After testing the MRAC combination PID, the hexacopter system was able to adapt to the constants Kp = 1.455, Ki = 1.3045 and Kd = 0.34. Environmental changes and component characteristics with system performance values rise time = 0.006 mS, Seating time = 0.0012.5 mS, oversoot = 5%, error study state = 0% , Delay time = 0.0038 mS, and Peak time = 0 .0068 mS.